Efektivitas Program Taxlive Dalam Meningkatkan Kesadaran Masyarakat : Studi Pada Direktorat Jenderal Pajak Kementerian Keuangan Republik Indonesia - Khafiyya, Azka (Prisani Cendekia Institute, 2024)
Taxpayers have a personal responsibility that must be carried out to an effort to fulfill all their rights and obligation in taxation. Even though taxpayers will continue to change over time, this obligation must still be fulfilled by the public as a sign of compliance with the rules and regulations set in Indonesia. This study aimed to determine there is an influence of TaxLive program on increasing public’s awareness to pay Tax. This study used quantitative research, with associative and descriptive approaches. The collecting data used questionnaire through google form that distributed to 101 respondents. Research questionnaire tested by using semantic differential measurement with 9 scales. The data analysis technique used SPSS software, which was explained descriptively. The questionnaire result tested by using simple linear regression and ANOVA. The result showed that Fvalue < Ftable (1.99 < 2.47), it can be concluded that Taxlive program hasn’t positive and significant influence on increasing public’s awareness to pay Tax.